The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s10639-021-10486-3
|View full text |Cite
|
Sign up to set email alerts
|

Online teaching self-efficacy during COVID-19: Changes, its associated factors and moderators

Abstract: Online teaching transition during COVID-19 school lockdown elicited challenges for teachers and schools across the globe. The existing literature on the impact of COVID-19 in the education sector is predominantly descriptive and focused on the difficulties faced by teachers during the process of transferring into online teaching, mainly in the higher education sector. This study adopted a mixed-method design to examine online teaching self-efficacy (TSE) during COVID-19, its associated factors and moderators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 54 publications
(75 reference statements)
7
148
0
8
Order By: Relevance
“…This may be explained by the teachers' lack of a clear range of strategies for interventions and management, which in turn may be explained by this never-before experienced situation of long-term online distance teaching. It seems that the teachers, lacking a clear representation of possible alternative teaching and relational strategies, failed to assess the potential solutions to this challenging teaching environment [26,27,[56][57][58]. Moreover, the data on scores on these self-related dimensions (self-esteem and self-efficacy for instructional strategies) points to a possible negative development, namely the failure to form positive and constructive coping responses and the inability to find possible active solutions to frustrating tasks or predicaments.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the teachers' lack of a clear range of strategies for interventions and management, which in turn may be explained by this never-before experienced situation of long-term online distance teaching. It seems that the teachers, lacking a clear representation of possible alternative teaching and relational strategies, failed to assess the potential solutions to this challenging teaching environment [26,27,[56][57][58]. Moreover, the data on scores on these self-related dimensions (self-esteem and self-efficacy for instructional strategies) points to a possible negative development, namely the failure to form positive and constructive coping responses and the inability to find possible active solutions to frustrating tasks or predicaments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study (Di Pietro et al, 2020) noted some elements that should be part of any successful strategies by the HEIs in integrating (online and offline) teaching-learning activities, to include; proper virtual learning environments (VLE), to guaranteeing access to internet and digital technologies for learning for the stakeholders, and teachers learning how to adapt their roles to situations in which they can effectively communicate with the students (e.g., to not lose motivation when shifting to the online learning platforms), through improved digital competences and pedagogical approaches (Mikheev et al, 2021;Raffaghelli et al, 2020) that are best suited for online learning and/or blended models such as the HyFlex + Tec model described in this study. To note, while Ma et al (2021) found that teachers' online teaching self-efficacy (TSE) in terms of technology-application for learning (Lin & Wang, 2021) increased during the Covid-19 lockdown. They (Ma et al, 2021) note that passion burnout (motivation) was a contributing factor towards the changes in online TSE for the teachers.…”
Section: Implications Of This Studymentioning
confidence: 99%
“…To note, while Ma et al (2021) found that teachers' online teaching self-efficacy (TSE) in terms of technology-application for learning (Lin & Wang, 2021) increased during the Covid-19 lockdown. They (Ma et al, 2021) note that passion burnout (motivation) was a contributing factor towards the changes in online TSE for the teachers. Interesting, the aforenoted observation also aligns with the results of this study where we note that users' emotions (positive or negative), and experiences for the teachers and students (see: Data Analysis and Results section) contributed to the energy levels (teaching-learning motivation), vice and versa.…”
Section: Implications Of This Studymentioning
confidence: 99%
“…Thus, as we saw in the first part of the section, although this period also offered great opportunities for expanding teaching skills in other learning environments, such as online, the existing literature on the impacts of COVID-19 on teaching has predominantly focused only on the difficulties faced by teachers during the process of transferring to online teaching [13]. Less attention has been paid to identifying and supporting the acquisition of teaching capacities that promote online teaching effectiveness.…”
Section: Aot During the Covid-19 Pandemicmentioning
confidence: 99%